PEMANFAATAN TANAH ADAT UNTUK KEPENTINGAN PENANAMAN MODAL DI BIDANG PERKEBUNAN (THE UTILITY OF THE CUSTOMARY LAND FOR INVESTMENT INTEREST IN THE PLANTATIONS FIELD) - Dian Cahyaningrum (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2012)
Plantations need land as the main capital. Land used for plantations sometimes include those land held by indigenous peoples for generations. Customary land acquisition for plantations should be done in consultation with indigenous peoples. But a lot of intrigue occurs during deliberations so that the takeovers of customary lands cause financial loss to the indigenous people. Even there was customary land that was given directly by the apparatus to the investor because it is considered belongs to the state. This happened because there is no formal legal evidence for the existence of customary land. To overcome the problem of customary land acquisition, various efforts should be made, such as amendment of agrarian law, revise Act No. 18/2004, provide guidance on indigenous peoples, applying patterns that do not transfer lands to investors, and impose sanctions on any person who committed acts against the law.ABSTRAKPerkebunan membutuhkan tanah sebagai modal utama. Lahan yang digunakan untuk perkebunan kadang-kadang dimiliki oleh masyarakat adat selama beberapa generasi. Pembebasan tanah adat untuk perkebunan harus dilakukan dengan konsultasi bersama masyarakat adat. Tapi banyak intrik terjadi selama musyawarah sehingga pengambilalihan tanah adat menyebabkan kerugian finansial kepada masyarakat adat. Bahkan ada tanah adat yang diserahkan langsung oleh aparat kepada investor karena dianggap milik negara. Hal ini terjadi karena tidak ada bukti hukum formal atas keberadaan tanah adat. Untuk mengatasi masalah pembebasan tanah adat, berbagai upaya harus dilakukan, seperti perubahan hukum agraria, merevisi UU No. 18/2004, memberikan bimbingan terhadap masyarakat adat, menerapkan pola yang tidak menyerahkan tanah kepada investor, dan menjatuhkan sanksi terhadap setiap orang yang melakukan perbuatan melawan hukum.